(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The article reviews the methods of diagnosing low-grade tumors. The combination of modern technologies and traditional methods in the diagnosis of this disease allows to increase the efficiency of diagnostics. In particular, the assessment of clinical symptoms, laboratory tests, imaging diagnostics, biopsy and genetic studies are widely covered. The study discusses the difficulties of diagnosis, the reliability of its results and the importance of timely diagnosis.